PERTIMBANGAN ETIKA DALAM PENGGUNAAN TEKNOLOGI HIJAU PADA KONSTRUKSI - Oktavianus Chayadi; Edison Hatoguan Manurung; Abdul Mubarok (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The construction industry contributes approximately 37–39% of global carbon dioxide emissions and consumes around 36% of total final energy, making it a priority sector in the sustainable development agenda. Green technology in construction offers solutions through the use of low-carbon materials, energy efficiency, and green building certification. However, the adoption of green technology cannot be separated from ethical considerations involving the professional responsibility of engineers, social justice, certification transparency, and respect for local communities. This study employs a conceptual literature-based approach to identify and analyze relevant engineering ethics dimensions in the implementation of green technology in Indonesia's construction sector. The findings indicate that engineering ethics must serve as the primary foundation for every green technology adoption decision, rather than merely fulfilling formal regulatory requirements. This study recommends integrating an engineering ethics framework into Indonesian green construction practice standards.